Research Anthology on Machine Learning Techniques, Methods, and Applications 2022
DOI: 10.4018/978-1-6684-6291-1.ch041
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Various Machine Learning Algorithms for Prediction of Insomnia

Abstract: An early diagnosis of insomnia can prevent further medical aids such as anger issues, heart diseases, anxiety, depression, and hypertension. Fifteen machine learning algorithms have been applied and 14 leading factors have been taken into consideration for predicting insomnia. Seven performance parameters (accuracy, kappa, the true positive rate, false positive rate, precision, f-measure, and AUC) are used and for implementation. The authors have used python language. The support vector machine is giving highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Prior studies have accurately predicted the presence of sleep disorders using machine-learning methods from a variety of datasets using numerous machine-learning methods [36][37][38]. Short-term insomnia detection was conducted using a single-channel sleep Electrooculography.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies have accurately predicted the presence of sleep disorders using machine-learning methods from a variety of datasets using numerous machine-learning methods [36][37][38]. Short-term insomnia detection was conducted using a single-channel sleep Electrooculography.…”
Section: Discussionmentioning
confidence: 99%
“…Short-term insomnia detection was conducted using a single-channel sleep Electrooculography. Furthermore, natural language processing on 18,901 tweets was conducted to find correlations between words related to insomnia and negative health information [38][39][40]. Furthermore, a comparative study of 15 machine learning algorithms identified 14 main factors for the prediction of insomnia, identifying that vision problems, mobility problems, and sleep disorders were significantly related to insomnia [38,39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation